2014
DOI: 10.1186/s13071-014-0462-1
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia lipoproteins: abundance, localisation and serology of Wolbachia peptidoglycan associated lipoprotein and the Type IV Secretion System component, VirB6 from Brugia malayi and Aedes albopictus

Abstract: BackgroundLipoproteins are the major agonists of Wolbachia-dependent inflammatory pathogenesis in filariasis and a validated target for drug discovery. Here we characterise the abundance, localisation and serology of the Wolbachia lipoproteins: Wolbachia peptidoglycan associated lipoprotein and the Type IV Secretion System component, VirB6.MethodsWe used proteomics to confirm lipoprotein presence and relative abundance; fractionation, immunoblotting and confocal and electron immuno-microscopy for localisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…1), which was significantly lower than the extent of upregulation due to Wolbachia infection (around 7-fold, P < 0.01). Voronin et al (2014) have shown that Wolbachia cell membrane contains the PGN-associated lipoprotein (PAL). PAL can specifically bind DAP (Parsons et al, 2006), indicating that DAP is present on the Wolbachia membrane.…”
Section: Discussionmentioning
confidence: 99%
“…1), which was significantly lower than the extent of upregulation due to Wolbachia infection (around 7-fold, P < 0.01). Voronin et al (2014) have shown that Wolbachia cell membrane contains the PGN-associated lipoprotein (PAL). PAL can specifically bind DAP (Parsons et al, 2006), indicating that DAP is present on the Wolbachia membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these data provide initial experimental evidence for an extracytoplasmic extended C-terminus in polytopic "extended VirB6-like proteins" in bacteria of the P-T4SS group. Moreover, antibodies reacting with VirB6-3 proteins from E. chaffeensis and Wolbachia species were detected in sera from dogs infected with E. chaffeensis (44) and in sera from humans infected with the filarial nematode Wuchereria bancrofti (38). This is additional evidence that in Rickettsiales this protein is not only surface exposed, but also induces immune responses.…”
Section: The Virb6-4::himar Mutant Has a Reduced Proliferation In Vitromentioning
confidence: 77%
“…Due to the C-terminal hydrophilic repeat domains of VirB6-3 and VirB6-4, the focus of this work, it has been proposed that these proteins or their C-terminal domains are surface exposed or proteolytically released into the host cell ( 15 ). In addition, evidence of surface exposure of the extended VirB6 proteins has been presented for other Rickettsiales ( 36 38 ). Hence, we confirmed their expression in infected HL-60 cells by Western immunoblotting and determined whether these proteins are surface exposed by trypsin digestion of intact A. phagocytophilum organisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently PAL was confirmed by proteomics as one of the most abundant proteins in extracts from adult B . malayi female worms [20].…”
Section: Introductionmentioning
confidence: 99%